2014
DOI: 10.1371/journal.pone.0092188
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Artificial MicroRNA Expressing AAV Vector for Phospholamban Silencing in Cardiomyocytes Improves Ca2+ Uptake into the Sarcoplasmic Reticulum

Abstract: In failing rat hearts, post-transcriptonal inhibition of phospholamban (PLB) expression by AAV9 vector-mediated cardiac delivery of short hairpin RNAs directed against PLB (shPLBr) improves both impaired SERCA2a controlled Ca2+ cycling and contractile dysfunction. Cardiac delivery of shPLB, however, was reported to cause cardiac toxicity in canines. Thus we developed a new AAV vector, scAAV6-amiR155-PLBr, expressing a novel engineered artificial microRNA (amiR155-PLBr) directed against PLB under control of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Thus, here we developed scAAV vectors expressing anti-adenoviral amiRs and analyzed their efficiency in the inhibition of hAd5 infection, first in vitro and then in vivo in immunosuppressed Syrian hamsters. This approach was chosen for several reasons: (1) scAAV vectors have a broad tissue tropism and enable rapid and strong transgene expression after transduction of the target cells in vitro and in vivo, 40 , 43 , 45 (2) amiRs can efficiently silence target genes and can easily be delivered from viral vectors including AAV vectors in vitro and in vivo, 46 , 47 , 48 , 49 but were reported to have lower toxicity than shRNAs, which are more commonly used in the context of viral vector-based gene-silencing investigations, 46 , 48 , 50 , 51 , 52 and (3) immunosuppressed Syrian hamsters represent an animal model that is permissive for hAd5. 18 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, here we developed scAAV vectors expressing anti-adenoviral amiRs and analyzed their efficiency in the inhibition of hAd5 infection, first in vitro and then in vivo in immunosuppressed Syrian hamsters. This approach was chosen for several reasons: (1) scAAV vectors have a broad tissue tropism and enable rapid and strong transgene expression after transduction of the target cells in vitro and in vivo, 40 , 43 , 45 (2) amiRs can efficiently silence target genes and can easily be delivered from viral vectors including AAV vectors in vitro and in vivo, 46 , 47 , 48 , 49 but were reported to have lower toxicity than shRNAs, which are more commonly used in the context of viral vector-based gene-silencing investigations, 46 , 48 , 50 , 51 , 52 and (3) immunosuppressed Syrian hamsters represent an animal model that is permissive for hAd5. 18 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the possible role of the endogenous miRNAs toward the SERCA/PLN complex in cardiomyocytes, the nanomolar affinity of ssDNA for PLN and its ability to reverse its inhibitory effects on SERCA constitutes a unique opportunity to exploit oligonucleotides as scaffolds for the design of small molecules to target Ca 2+ regulation. While DNA aptamers or miRNA constructs have been successfully used to target and regulate the PLN gene 11 41 , silencing or ablation of the PLN gene has resulted in cardiomyopathies. In contrast, tunable regulation of PLN inhibitory function of SERCA by oligonucleotide-based drugs may represent a more promising therapeutic avenue in which the extent of SERCA activation can be fine-tuned to match the pathological insult.…”
Section: Discussionmentioning
confidence: 99%
“…Among cardiovascular diseases, hypertension and heart failure have been treated with amiRNAs (Fan et al, 2012; Größl et al, 2014). The aim of the first study was to determine whether mir‐155‐based AT1aR (angiotensin II type 1 receptor, overexpressed in spontaneously hypertensive rats) amiRNA could impair hypertension and improve cardiovascular remodeling in spontaneously hypertensive rats.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Despite decreased amiRNA expression, both RNAi triggers reduced PLB expression equally and enhanced Ca2+ transport. Proteomic analysis showed that the shRNA induced the expression of interferon‐regulated and proinflammatory genes whereas artificial miRNA did not induce any of them (Größl et al, 2014).…”
Section: Other Diseasesmentioning
confidence: 99%